ANATOMI AKAR KECUBUNG (Datura metel L.) SETELAH TERPAPAR LOGAM BERAT TEMBAGA - , DENIS HERLIN SAPUTRI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Copper is one of metals that are structurally stable. Nowadays the used of copper has been increasing dramatically. It caused the increasing of copper in the environment to the toxic levels for organisms. Plants are organisms that are more sensitive to the environmental changes than animals and humans. Datura metel L. is one of the heavy metals tolerant plants and has the potential as phytoremediation agent. Therefore the aim of this study was to learn about the anatomyof Datura metel L. exposed by Copper. Datura seedlings were treated with heavy metal with doses of 100, 1000, 2000, 2500 ppm and control,for the duration of 12, 36, 84, and 132 hours. Roots anatomical observation, were done with paraffin method. Cross-section of the roots was done by rotary microtome. The results showed that diameter of roots and area of xylem increased at the end of treatment (132 hours), but the number and diameter of trachea decreased with the increases of doses and duration of copper exposure, the thickness of endodermis tissues in the primary structure were found in the early time of copper exposure, and the secondary development of tissues became induced by the increasing of copper doses. The results indicated that Datura metel L. had the tolerant against high level of copper, because the plant hadsurvival mechanisms against the toxicity of copper.